Kira jako (nie)obcy. O protagoniście mangi Death Note Takeshi Obaty i Tsugumi Ohby - Dobrzycki, Jarosław (Paidia i Literatura, 2020)
The article analyzes the alienation of the main character of the manga series Death Note, who owns the Death Notebook referred to in the title. The said notebook allows to kill any person. Drawing upon the theses of Michel Foucault related to the rights of monarchs of bygone times to condemn individuals to death, and to ritualizing death itself, the author of the article shows Kira as a continuator of the said monarchs. The motif of death from the hands of another person is indicated as a form of revenge for harms suffered by one, based on considerations by Jean Baudrillard. The text also aims to show that comic books are not just entertainment for the masses, but can convey serious content instead.